Meta Analysis: Fungal Distribution in the Large Intestine - Amiroh Tus Sholeha M; Syamsu Rijal; Muh. Irwan Gunawan (Newinera Publisher, 2026)
The human colon hosts a diverse microbial ecosystem, including fungi (mycobiome), which, although comprising a small proportion of the microbiota, play a crucial role in maintaining gut homeostasis, metabolism, and immune regulation. Imbalances in fungal communities are associated with gastrointestinal disorders such as inflammatory bowel disease and colorectal cancer. This study employed a systematic literature review with meta-analysis following PRISMA guidelines. Data were collected from major databases (2015–2025) using PICO-based keywords. Eligible studies were analyzed using statistical software to calculate pooled effect sizes, heterogeneity (I²), and significance levels. A random-effects model was applied due to high variability among studies. Five studies were included, revealing that fungi are consistently present across all colon segments, with dominant genera including Candida and Saccharomyces. The pooled effect size (0.125; 95% CI: 0.005–0.248; p < 0.001) confirms a stable fungal presence. However, heterogeneity was very high (I² = 97.85%), influenced by differences in populations, methodologies, and disease conditions. Findings highlight the role of fungi in microbial interactions, inflammation, and potential use as biomarkers in gastrointestinal diseases. Colonic fungi are integral to gut health, though highly variable across individuals. Further standardized and longitudinal research is needed to clarify their clinical significance and therapeutic potential.